An in-depth analysis of original antigenic sin in dengue virus infection - Midgley, C; Bajwa-Joseph, M; Vasanawathana, S; Limpitikul, W; Wills, B; Flanagan, A; Waiyaiya, E; Tran, H; Cowper, A; Chotiyarnwong, P; Grimes, J; Yoksan, S; et al. (American Society for Microbiology, 2010)
The evolution of dengue viruses has resulted in four antigenically similar yet distinct serotypes. Infection with one serotype likely elicits lifelong immunity to that serotype, but generally not against the other three. Secondary or sequential infections are common, as multiple viral serotypes frequently cocirculate. Dengue infection, although frequently mild, can lead to dengue hemorrhagic fever (DHF) which can be life threatening. DHF is more common in secondary dengue infections, implying a role for the adaptive immune response in the disease. There is currently much effort toward the design and implementation of a dengue vaccine but these efforts are made more difficult by the challenge of inducing durable neutralizing immunity to all four viruses. Domain 3 of the dengue virus envelope protein (ED3) has been suggested as one such candidate because it contains neutralizing epitopes and it was originally thought that relatively few cross-reactive antibodies are directed to this domain. In this study, we performed a detailed analysis of the anti-ED3 response in a cohort of patients suffering either primary or secondary dengue infections. The results show dramatic evidence of original antigenic sin in secondary infections both in terms of binding and enhancement activity. This has important implications for dengue vaccine design because heterologous boosting is likely to maintain the immunological footprint of the first vaccination. On the basis of these findings, we propose a simple in vitro enzyme-linked immunosorbent assay (ELISA) to diagnose the original dengue infection in secondary dengue cases. Dengue virus is an insect-borne flavivirus transmitted to humans by the bite of an infected mosquito, usually Aedes aegypti (20). There are four circulating serotypes of dengue (dengue serotype 1 [Den1] to Den4) that show up to 70% sequence homology across their genomes (4, 17), and it is common for multiple viral serotypes to cocirculate in countries where dengue is endemic. Most dengue infections are either asymptomatic or lead to uncomplicated dengue fever (DF). However, in 1 to 5% of cases, symptoms can be more severe with the development of plasma leakage and hemorrhage. Such dengue hemorrhagic fever (DHF) can lead to circulatory collapse, resulting in a mortality rate of around 20% if left untreated. The more frequent occurrence of DHF in secondary dengue infections in children and adults suggests a role for the acquired immune system in disease pathogenesis, and there has been considerable research into both the B- and T-cell responses. Antibody-dependent enhancement (ADE) of infection, proposed by Halstead in 1977 (24, 25), is one hypothesis for this increase in severity in secondary infections (23, 36). During a primary infection, antibodies that cross-react with the remaining 3 serotypes are induced. After a few months, when heterologous protection is no longer observed (54), it is hypothesized that these cross-reactive antibodies decline to subneutralizing levels, meaning that a heterologous infecting serotype is not controlled. Antibody made against the primary infecting virus may not be of sufficient avidity to neutralize a second serotype. Instead, these poorly neutralizing, low-avidity cross-reactive antibodies bind the secondary virus and target it to Fcγ receptor-bearing cells, such as macrophage/monocytes (24, 25), leading to internalization and increased virus replication. In vivo, ADE has been shown to induce lethal disease in mice (2) and to drive high virus loads in primates (16, 22). ADE has also been invoked to explain a peak in disease severity in primary cases during the first year of life, as the titers of passively transferred maternal antibody fall (23, 35, 41, 56). The incidence of dengue increased sharply in the middle of the last century and is still increasing at an alarming rate (20). There are estimated to be around 3.6 billion people living in the tropics and subtropics who are at risk from dengue, with up to 50 million predicted infections per annum. To date, however, there are no specific treatments for dengue barring careful attention to fluid replacement. The scale of the problem posed by dengue has spawned much interest in the development of a dengue vaccine, with some candidates in phase II trials (67, 69), and also in anti-dengue drugs that have not yet reached clinical trials. A number of vaccine candidates, ranging from live attenuated viruses to subunit vaccines, are currently being pursued. The envelope (E) protein of dengue is a major target of neutralizing (48, 53, 62) and protective antibodies (32) and, as such, should be a key component for any subunit vaccines. The envelope protein consists of three domains: ED1, ED2, and ED3 (38, 47, 48). ED3 is proposed to be the binding domain for the virus (7, 9, 28), attaching to as yet poorly characterized cellular receptor(s); although heparan sulfate has been implicated in the interaction (29). Indeed, in mice, anti-ED3 monoclonal antibodies are potent neutralizers of dengue virus (5, 18, 19, 27, 43, 52, 55, 60, 61); often neutralizing to greater levels than those targeting ED1 or ED2 (60). ED3 is a target of both serotype-specific (5, 18, 42, 45, 53, 55, 60, 61) and cross-reactive (19, 43, 46, 52, 55, 60, 61) neutralizing antibodies. Of the anti-ED3 antibodies that are strongly neutralizing, however, the majority are usually serotype specific (5, 55, 60), and cross-reactive antibodies are generally weaker neutralizers (19, 61). There have been a number of vaccination studies investigating ED3 as a potential immunogen (3, 30, 57-59). In this study, we have performed a detailed analysis of the anti-ED3 antibody responses in humans, using a cohort of patients experiencing either primary or secondary dengue infections. We demonstrate that low-level dengue cross-reactive anti-ED3 responses are induced upon primary infection and boosted dramatically during a secondary heterotypic infection. We have developed a competition enzyme-linked immunosorbent assay (ELISA) to measure the relative avidities of these cross-reactive antibodies and show that the response is dominated by original antigenic sin. We propose this ELISA as a simple diagnostic test for determining the serotype of the original dengue infection in secondary dengue cases. Furthermore, we go on to show an inverse relationship between the avidity of the antibody response and enhancing activity.